Espectrando: proposta de utilização de uma sequência didática para o ensino de espectroscopia de estrelas - Barreto, Tatiane Bitencourt (2020)
In this Dissertation is proposed a Didactic Sequence called "Espectrando", which its primary purpose consists in to teach stellar spectroscopy through a Didactic Sequence. The Didactic Sequence was elaborated to study the stellar classification from their spectra through activities elaborated to be imployed for teachers at different teaching levels. The Didact Sequence was applied to a group of eleven teachers in order to capacity them to use didactical resources adquetaley to teach specific astronomy concepts as well as to motivate and lead them to rethink as to discuss the topics related to the Astronomy in the classrooms as well as to incentive the use of new methodologies and strategies in their daily practice. Besides, we also evaluated the application of the activities of our Didactic Sequence not only concerning the answers but also aspects of its conceptions. The product elaborated called “Espectrando” constituted an alternative tool and a critical methodological resource to understand the relations among the main physical properties of a star (its brightness, size, colour, chemical composition, among others).